Improving Studentsâ Speaking Skill through Information Gap at the Twelfth Grader Studentsâ of the Vocational School in Pontianak - Sitinjak, Rosalina (West Kalimantan Scholars: Studies on English Language and Education, 2015)
The aims of this classroom action research are to find out how can and how well the information gap improves the studentsâ speaking skill at one vocational high school in Pontianak.Tools of data collection were observation checklist table, field note and speaking test. The participants of this research were the students of the twelfth grade of one vocational high school in Pontianak who were selected purposively. The findings showed that the studentsâ speaking skill has been improved by using information gap technique where the studentsâ behavior during the treatment was changed that were reflected from their responses, creativities, and speaking performance. The studentsâ speaking test results showed that in the first cycle, the studentsâ mean score was 55.00, then in the second cycle became 60.62, and the last cycle it became 72.07. Based on these findings, English teacher should consider using this technique to improve studentsâ speaking skill.